Toxicity assessment of crude and partially purified extracts of marine Synechocystis and Synechococcus cyanobacterial strains in marine invertebrates - Martins, Rosario (2015)
Among the Cyanoprokaryota, the genera Synechocystis and Synechococcus have rarely been studied with respect to potential toxicity. This is particularly true with marine environments where studies about the toxicity of cyanobacteria are restricted to filamentous forms at the warmer temperate and tropical regions and also to filamentous forms at cold seas such as the Baltic Sea. In this study, we describe the effects of cyanobacterial strains of the Synechocystis and Synechococcus genera isolated from the marine coast of Portugal, on marine invertebrates. Crude and partially purified extracts at a concentration of 100 mg/ml of freeze-dried material of the marine strains were tested for acute toxicity in nauplii of the brine shrimp Artemia salina, in the rotifer Brachionus plicatillis and in embryos of the sea urchin Paracentrotus lividus and the mussel Mytilus galloprovincialis. The cyanobacterial extracts, especially the crude extract, had an impact on A. salina nauplii. No significant toxic effects were registered against the rotifer. A negative impact of all strains was recorded on the embryonic development of the sea urchin, with toxic effects resulting in an inhibition of embryogenesis or development of smaller larvae. To the mussel embryos, the effects of cyanobacterial extracts resulted in a complete inhibition of embryogenesis. The results of all assays indicate that Synechocystis and Synechococcus marine strains contained toxic compounds to marine invertebrates.